Cardiac monitoring of high-dose verapamil in cluster headache: An international Delphi study. (December 2016) - Koppen, H; Stolwijk, J; Wilms, EB; van Driel, V; Ferrari, MD; Haan, J
Background: In many patients, high-dose verapamil (HDV) is the only effective prophylactic treatment for cluster headache. Although cardiac adverse events and EKG abnormalities are relatively common, evidence-based guidelines for screening and monitoring patients on HDV are lacking. Goal and methods: Using the Delphi approach, we interviewed 22 international clinical experts in cardiac rhythm disorders to formulate EKG guidelines for the pretreatment screening and monitoring of cluster headache patients using HDV. Results: The panel agreed only on performing pretreatment EKG to screen for pre-existing cardiac arrhythmia. Pretreatment EKG was deemed not necessary by most panel members for patients who did not have cardiac adverse events during a previous period of cluster headache attacks treated with HDV. Half the panel advised Holter EKG for patients on verapamil ≥ 480 mg/day. The highest recommended daily doses varied between 240 and 960 mg. Contraindications for use of verapamil largely followed FDA guidelines. Discussion: Experts in cardiac rhythm disorders agreed on pretreatment EKG monitoring, but no consensus was reached on EKG monitoring during HDV treatment and around dose adjustments.